Hubungan Stres Dengan Kualitas Tidur Pada Pasien Kanker Yang Menjalani Kemoterapi Pada Saat Pandemi Covid-19 Di RSUP Dr. M.Djamil Padang - Weny Amelia; Lola Despitasari; Fitria Alisa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
The condition of the COVID-19 pandemic is a threatening condition for cancer sufferers. Management of cancer patients can be done by surgery, chemotherapy, radiotherapy and hormone therapy to treat cancer. For cancer patients infected with COVID-19, adequate protective equipment is needed. Symptoms of COVID-19 that cause people to suffer from cancer or are being treated for cancer that can be more severe, such as high fever, chest pain, bluish lips and nails, shortness of breath, to loss of consciousness or coma. The process during treatment for cancer can affect the psychological health and physical health of patients in the form of illness, stress, illness and sleep disorders. The purpose of this study was to see the relationship between stress and sleep quality in cancer patients undergoing chemotherapy during the Covid-19 pandemic at Dr. M. Djamil Padang. This type of research is the type of research used is a survey analysis, namely to see the events studied using the research design used is a cross sectional study. The sample in this study were breast cancer patients who underwent chemotherapy during the Covid-19 pandemic with accidental sampling technique. The stress instrument uses the DASS (Depressi On Anxiety Stress Scale) 42 which consists of 14 questions about stress, while the sleep quality instrument uses the Pitssburgh Sleep Quality Index (PSQI) questionnaire. The questionnaire consisted of 18 questions including seven components of sleep quality, sleep latency, sleep duration, sleep disturbances, use of sleeping pills, and daytime activity dysfunction. The results of this study were processed using the Chi-Square test. The results showed a relationship between stress and sleep quality in cancer patients undergoing chemotherapy during the Covid-19 pandemic (p value = 0.000; α = 0.05).